Círculos dialógicos investigativo-formativos com professores do ensino médio: por uma proposta institucional de formação permanente com professores - Vieira, Andréa Oliveira (2019)
This dissertation is inside of the research line 2 (LP2): pedagogic management and educational contexts, part of professional master‟s in public policies and educational management. The aim of this study and, consequently, the proposition, are inside to the management in teacher‟s formation, specifically the permanent teacher´s formation, presenting as protagonists teachers of high school and the management team of an educational institute. The objective is to elaborate theoretical and practical principles for the construction of a permanent formation proposal with MS teachers which interwines the specific knowledge of teaching areas with the demands of teaching in the 21st Century. The qualitative research, with a dialogic-investigative perspective, used as source to this dissertation was developed in a school of private network teaching in Santa Maria- Rio Grande do Sul-Brasil. The protagonists were high school teachers, which were invited to participate in a voluntary way, with the etic compromise to hiding their identities. The investigative route was heading by investigative dialogic curriculum, proposed by Henz (2015), as well as Josso (2010), Freire (2001, 2013) Assamm (2007), Imbernón ( 2010, 2016), Maciel (2000, 2009, 2012) . Bringing the formation necessities identified by high school teachers. The results composed resources to design an institutional propose of permanent formation, clearly dialogic, dynamic end reflexive, with focus in formative necessities related to this level of Basic Education.